Comparative study on boundary lubrication of Ti3C2T x MXene and graphene oxide in water - Wei Sun; Qingrui Song; Kun Liu; Qing Zhang; Zhensheng Tao; Jiaxin Ye (Friction)
Abstract The emerging use of two-dimensional (2D) nanomaterials as boundary lubricants in water offers numerous benefits over oil-based lubricants; whereas the friction reduction varies significantly with nanomaterial type, size, loading, morphology, etc. Graphene oxide (GO) and Ti3C2T x MXene, a relatively new 2D material, are investigated as boundary lubricants in water in this study. The contact pair mainly includes Si3N4 balls and Si wafer. The results found (1) monodispersed GO offers better lubricity than monodispersed MXene under identical concentration and testing conditions; and (2) the mixed dispersion of GO and MXene (0.1 mg/ml: 0.1 mg/ml) produced the lowest friction coefficient of ∼ 0.021, a value 4× and 10× lower than that produced by comparable mono-dispersions of GO or MXene, respectively. Wear track analysis, focused ion beam microscopy, in-situ contact observation, and atomic force microscopy (AFM) characterization suggest (1) GO nanoflakes have higher adhesion than MXene and are more easily adsorbed on the tribopairs’ surfaces, and (2) GO/MXene tribofilm has a layered nanostructure constituting GO, MXene, amorphous carbon, and TiO2. We further hypothesized that the high lubricity of GO/MXene results from the synergy of GO’s high adhesiveness, MXene’s load support ability, and the low shear strength of both constituents. The present study highlights the key role of tribofilm stability in water-based boundary lubrication using state-of-the-art 2D nanomaterials.